2022
DOI: 10.3389/fnins.2022.866899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Organophosphate Toxicity and Anti-cholinergics on Electroencephalogram and Respiratory Mechanics in Mice

Abstract: Organophosphates are used in agriculture as insecticides but are potentially toxic to humans when exposed at high concentrations. The mechanism of toxicity is through antagonism of acetylcholinesterase, which secondarily causes excess activation of cholinergic receptors leading to seizures, tremors, respiratory depression, and other physiological consequences. Here we investigated two of the major pathophysiological effects, seizures and respiratory depression, using subcutaneous injection into mice of the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…High-fat-diet has been shown to impact diabetes ( da Cruz et al, 2022 ), hypertension ( Logvinov et al, 2021 ), obesity ( Kang et al, 2022 ), and respiratory diseases ( Li et al, 2021a ). Organophosphate pesticides (and pesticides in general) have been shown to impact diabetes ( Miranda et al, 2022 ), hypertension ( Ledda et al, 2015 ), obesity ( Miranda et al, 2022 ), and respiratory diseases ( Bugay et al, 2022 ), and heavy metals have been shown to impact diabetes ( Wang et al, 2022 ), hypertension ( Tang et al, 2022a ), obesity ( Duc et al, 2022 ), and respiratory diseases ( Yao et al, 2021 ). More data are required to state with confidence that there are strong overlaps between the CFs to COVID-19 and its comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…High-fat-diet has been shown to impact diabetes ( da Cruz et al, 2022 ), hypertension ( Logvinov et al, 2021 ), obesity ( Kang et al, 2022 ), and respiratory diseases ( Li et al, 2021a ). Organophosphate pesticides (and pesticides in general) have been shown to impact diabetes ( Miranda et al, 2022 ), hypertension ( Ledda et al, 2015 ), obesity ( Miranda et al, 2022 ), and respiratory diseases ( Bugay et al, 2022 ), and heavy metals have been shown to impact diabetes ( Wang et al, 2022 ), hypertension ( Tang et al, 2022a ), obesity ( Duc et al, 2022 ), and respiratory diseases ( Yao et al, 2021 ). More data are required to state with confidence that there are strong overlaps between the CFs to COVID-19 and its comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Acute OP intoxication leads to accumulation of acetylcholine and hyperstimulation of the cholinergic pathway both in the peripheral and the central nervous system (CNS), resulting in cholinergic crisis (Hulse et al 2014 ). Without intervention, the primary cause of death from OP-induced cholinergic crisis is respiratory failure (Bugay et al 2022 ; Dube et al 1993 ; Gaspari and Paydarfar 2007 ; Hulse et al 2014 ). Cardiovascular collapse from direct effects of OP on the cardiovascular system also contribute to fatal outcomes (McFarland and Lacy 1968 ; Munidasa et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%